2013
DOI: 10.1257/app.5.2.29
|View full text |Cite
|
Sign up to set email alerts
|

School Inputs, Household Substitution, and Test Scores

Abstract: Empirical studies of the relationship between school inputs and test scores typically do not account for household responses to changes in school inputs. Evidence from India and Zambia shows that student test scores are higher when schools receive unanticipated grants, but there is no impact of grants that are anticipated. We show that the most likely mechanism for this result is that households offset their own spending in response to anticipated grants. Our results confirm the importance of optimal household… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
109
4
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(128 citation statements)
references
References 46 publications
11
109
4
4
Order By: Relevance
“…To shed light on these questions, Table 6 reports the effect of the grant programme on household characteristics (panel A), teacher characteristics (panel B), and school characteristics (panel C). While other studies in developing countries have shown that households may act as either substitutes or complements to school investments (Das et al 2013), we find virtually no effect of school grants on parental expenditure on schooling (tuition, uniforms, supplies) for either grade or either region, nor any effect on whether the student has a tutor. While other studies in developing countries have shown that households may act as either substitutes or complements to school investments (Das et al 2013), we find virtually no effect of school grants on parental expenditure on schooling (tuition, uniforms, supplies) for either grade or either region, nor any effect on whether the student has a tutor.…”
Section: Understanding the Differences By Grade And Regioncontrasting
confidence: 99%
See 2 more Smart Citations
“…To shed light on these questions, Table 6 reports the effect of the grant programme on household characteristics (panel A), teacher characteristics (panel B), and school characteristics (panel C). While other studies in developing countries have shown that households may act as either substitutes or complements to school investments (Das et al 2013), we find virtually no effect of school grants on parental expenditure on schooling (tuition, uniforms, supplies) for either grade or either region, nor any effect on whether the student has a tutor. While other studies in developing countries have shown that households may act as either substitutes or complements to school investments (Das et al 2013), we find virtually no effect of school grants on parental expenditure on schooling (tuition, uniforms, supplies) for either grade or either region, nor any effect on whether the student has a tutor.…”
Section: Understanding the Differences By Grade And Regioncontrasting
confidence: 99%
“…13 We present separate estimates of programme impacts for grade 3 (column (1)), grade 5 (column (2)) and the difference (column (3)), as well as impacts in the south (column (4)), north (column (5)) and the difference (column (6)). It is noteworthy that unlike Das et al (2013), we do not find strong evidence of a parental response, even in the short run. Students also do not appear to substitute away from or towards labour as measured by whether they work after school or miss school (though there is a small marginally significant effect on missing school in the south).…”
Section: Understanding the Differences By Grade And Regioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Shi (2012) documents a flypaper effect in the context of a change in school fees in rural China. Conversely, Das et al (2013) find crowd-out of household educational expenditures in response to anticipated public grants to schools. The Angrist et al (2002) study of Colombian private school vouchers comes closest to finding crowd-in in response to a subsidy, but that paper does not provide a formal statistical test of the hypothesis that household educational expenditures rose by more than the value of the subsidy.…”
Section: Introductionmentioning
confidence: 90%
“…A related but distinct literature has also emerged in the past decade evaluating various interventions for the low productivity of Indian schools, for example through incentives paid to teachers for greater attendance (Duflo, Hanna, & Ryan, 2012), computer-assisted learning (Banerjee, Cole, Duflo, & Linden, 2007), para-teachers (Atherton & Kingdon, 2010, Banerjee et al, 2007Muralidharan & Sundararaman, 2012), performance-based incentives to teachers (Muralidharan & Sundararaman, 2011), diagnostic feedback to teachers (Muralidharan & Sundararaman, 2010) and block grants to schools (Das et al, 2013).…”
Section: Schooling For Young Children In Indiamentioning
confidence: 99%